Reviewing the situation: men and antiretroviral treatment in Soweto, South Africa - Struthers, Helen Elizabeth (My University, 2015)
There have been great strides in increasing access to antiretroviral treatment for HIV-positive people in South Africa. However it has been observed that men are not accessing treatment to the same extent as women. In Soweto only 30% of the people accessing treatment are men, where the expected rate would be around 45%. Whilst there have been some studies observing treatment uptake, they do not explain the behavioural component.
Keywords: Men; Antiretroviral Therapy, Highly Active; HIV